(untitled) (Philology, 2026)
The paper discusses the various teaching methods and strategies concerning Korean language learning. The main focus is on the problems that arise between effective and ineffective learners and the reasons for them. The strategies are discussed in great detail and the differences between the two groups are explained through an exhaustive survey.